2012
DOI: 10.2174/2212798411204010050
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Hypoglycemic Effects of Five Commonly Used Herbal Food Supplements

Abstract: Hyperglycemia is a pathological condition associated with prediabetes and diabetes. The incidence of prediabetes and diabetes is increasing and imposes great burden on healthcare worldwide. Patients with prediabetes and diabetes have significantly increased risk for cardiovascular diseases and other complications. Currently, management of hyperglycemia includes pharmacological interventions, physical exercise, and change of life style and diet. Food supplements have increasingly become attractive alternatives … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
21
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 52 publications
2
21
0
1
Order By: Relevance
“…For centuries, cinnamon has been a popular spice used by different cultures around the world (Ranasinghe et al, 2013), and it is among the best-selling herbal dietary supplements as recently reported (Andrew & Izzo, 2017). Cinnamon is an herbal remedy used traditionally by patients with PCOS to improve their menstrual cycle (Bandara, Uluwaduge, & Jansz, 2012;Deng, 2012). In traditional Persian medicine (Hashempur, Khademi, Rahmanifard, & Zarshenas, 2017) It is obtained from the inner bark of the cinnamomum tree (Deng, 2012;Wickenberg, Lindstedt, Berntorp, Nilsson, & Hlebowicz, 2012).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For centuries, cinnamon has been a popular spice used by different cultures around the world (Ranasinghe et al, 2013), and it is among the best-selling herbal dietary supplements as recently reported (Andrew & Izzo, 2017). Cinnamon is an herbal remedy used traditionally by patients with PCOS to improve their menstrual cycle (Bandara, Uluwaduge, & Jansz, 2012;Deng, 2012). In traditional Persian medicine (Hashempur, Khademi, Rahmanifard, & Zarshenas, 2017) It is obtained from the inner bark of the cinnamomum tree (Deng, 2012;Wickenberg, Lindstedt, Berntorp, Nilsson, & Hlebowicz, 2012).…”
mentioning
confidence: 99%
“…Cinnamon is an herbal remedy used traditionally by patients with PCOS to improve their menstrual cycle (Bandara, Uluwaduge, & Jansz, 2012;Deng, 2012). In traditional Persian medicine (Hashempur, Khademi, Rahmanifard, & Zarshenas, 2017) It is obtained from the inner bark of the cinnamomum tree (Deng, 2012;Wickenberg, Lindstedt, Berntorp, Nilsson, & Hlebowicz, 2012).…”
mentioning
confidence: 99%
“…In addition, it was evidenced that fenugreek (extracts) stimulates insulin secretion and/or activity and its receptor expression, and thereby improves diabetes mellitus wound healing. 10,12,21 In our experimental series, granulocytes and total white blood cell counts were augmented. This event might explain Patil et al, 18 reported allergic reaction following fenugreek usage, in some clinical cases.…”
Section: Discussionmentioning
confidence: 80%
“…[4][5][6][7][8] Other T. foenum-graecumfractions modulate blood sugar levels and insulin secretion and thereby ameliorate the woundhealing and prevent diabetes. [9][10][11][12] The anti-obesity effect of fenugreek might be bypassed through repressing adipocytes' proliferation and lipids metabolism. 13,14 It also stimulates anti-oxidative enzymes activities and decreases the ROS release, a major protective pathway against several pathologies.…”
Section: Introductionmentioning
confidence: 99%
“…support the ability of these combined agents to effectively lower blood glucose levels. Nevertheless, the usage of these herbal food supplements should not be discounted by healthcare professionals now that they are becoming increasingly popular, especially for those whose blood glucose levels are on the borderline and pharmacological therapies have not been initiated (Deng 2012).…”
mentioning
confidence: 99%